The Gap in Public Understanding of Law Number 10 of 2016 on Regional Head Elections at the Regency Level: Efforts toward Legal Dissemination - Satria Prayoga; Agung Budi Prastyo; Syamsir Syamsu; Ahmad Rifai (Universitas Negeri Gorontalo, 2025)
Regional Head Elections (Pilkada) are a fundamental mechanism for strengthening local democracy and citizen participation. However, public understanding of the legal framework for regional elections often experiences gaps, resulting in uneven participation and a lack of public legal awareness. This study aims to: (1) analyze the level of public understanding of Law No. 10 of 2016 on Pilkada, (2) identify the effectiveness of legal socialization programs in increasing democratic awareness, and (3) formulate policy recommendations for strengthening legal education on Pilkada at the local level. The research method used a qualitative approach through focus group discussions (FGD) and in-depth interviews with the community of Pekon Tegalsari as the main participants, as well as analysis of related policy documents. The data were analyzed using thematic analysis to identify patterns of gaps in understanding and obstacles to socialization. The results of the study show that there is a significant gap between the design of election policies and public understanding, especially in terms of the rights and obligations of voters. Existing socialization programs have not been optimal in reaching all segments of society, especially marginalized groups. These findings emphasize the importance of an inclusive approach to legal socialization, involving synergy between local governments, educational institutions, local media, and civil society organizations to strengthen democratic legal awareness and active participation in elections.